1999
DOI: 10.1103/physrevlett.82.5249
|View full text |Cite
|
Sign up to set email alerts
|

Inertial Effects on Fluid Flow through Disordered Porous Media

Abstract: We investigate the origin of the deviations from the classical Darcy law by numerical simulation of the Navier-Stokes equations in two-dimensional disordered porous media. We apply the Forchheimer equation as a phenomenological model to correlate the variations of the friction factor for different porosities and flow conditions. At sufficiently high Reynolds numbers, when inertia becomes relevant, we observe a transition from linear to nonlinear behavior which is typical of experiments. We find that such a tra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
155
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 234 publications
(168 citation statements)
references
References 16 publications
13
155
0
Order By: Relevance
“…Moreover, photoelastic visualization experiments [36] and simulations [13,38,39] have shown that the contact forces are strongly localized along "force chains" which carry most of the applied stress. To quantify the degree of force localization, we consider the participation number Γ [40]:…”
Section: Force Distributions Force Chains and Participation Numbermentioning
confidence: 99%
“…Moreover, photoelastic visualization experiments [36] and simulations [13,38,39] have shown that the contact forces are strongly localized along "force chains" which carry most of the applied stress. To quantify the degree of force localization, we consider the participation number Γ [40]:…”
Section: Force Distributions Force Chains and Participation Numbermentioning
confidence: 99%
“…The second is that of Forchheimer (see Nield & Bejan [77]) with non-linear drag terms lvlvi and lvl 2 vi such that 6) where {3 1 and {3 2 are some constants of proportionality.…”
Section: Governing Equationsmentioning
confidence: 99%
“…7)), the symmetric matrix representation z 2 Dt(q;) can be derived, where, letting M= z 2 Dt(c/J), (2i-3)(2i-1)(2i + 1)(2i + 3)(2i + 5) 6 (2i-1)(2i + 1)(2i + 3)(2i + 5)(2i + 7) -2(i + 3)(i + 2) (2i + 1)(2i + 3)(2i + 5)(2i + 7)(2i + 9) where M is of bandwidth 8.…”
Section: C3 Calculation Of Z 2 Dt( Cjj)mentioning
confidence: 99%
“…The inertial effect became smaller at the volume fraction approaching close packing. Two-dimensional simulation considering inertia was also studied by Andrade et al (1999). The porous medium was created by using square plaquettes as obstacles for fluid flow.…”
Section: Introductionmentioning
confidence: 99%
“…The Forchheimer equation can be modified as friction factor and Reynolds number correlation (Andrade et al, 1999):…”
mentioning
confidence: 99%